Math, asked by XxBrainlyQuestionerX, 9 days ago

Let the required point be ( 0 , y ) . Note that x coordinate will be zero because point lies on y axis. Now this point is at distance 10 from ( 6 ,6 ) , so use distance formula \begin{gathered} \sqrt{(0 - 6) {}^{2} + (y - 6) {}^{2} } = 10 \\ \\ \implies 36 + (y - 6) {}^{2} = 100 \\ \\ \implies (y - 6) {}^{2} = 100 - 36 = 64 \\ \\ \implies y - 6 = \sqrt{64} = \pm8 \\ \\ y = 6 + 8 \: \: or\: \: 6 - 8 \\ \\ y = 14 \: \: \: or \: \: - 2\end{gathered}(0−6)2+(y−6)2​=10​

Answers

Answered by Renumahala2601
2

Answer:

Let the required point be ( 0 , y ) . Note that x coordinate will be zero because point lies on y axis. Now this point is at distance 10 from ( 6 ,6 )

, so use distance formula

\begin{gathered} \sqrt{(0 - 6) {}^{2} + (y - 6) {}^{2} } = 10 \\ \\ \implies 36 + (y - 6) {}^{2} = 100 \\ \\ \implies (y - 6) {}^{2} = 100 - 36 = 64 \\ \\ \implies y - 6 = \sqrt{64} = \pm8 \\ \\ y = 6 + 8 \: \: or\: \: 6 - 8 \\ \\ y = 14 \: \: \: or \: \: - 2\end{gathered} </p><p>(0−6) </p><p>2</p><p> +(y−6) </p><p>2</p><p> </p><p>	</p><p> =10

Answered by BrainlyFather0001Fan
0

Answer:

\begin{gathered} \sqrt{(0 - 6) {}^{2} + (y - 6) {}^{2} } = 10 \\ \\ \implies 36 + (y - 6) {}^{2} = 100 \\ \\ \implies (y - 6) {}^{2} = 100 - 36 = 64 \\ \\ \implies y - 6 = \sqrt{64} = \pm8 \\ \\ y = 6 + 8 \: \: or\: \: 6 - 8 \\ \\ y = 14 \: \: \: or \: \: - 2\end{gathered} </p><p>(0−6) </p><p>2</p><p> +(y−6) </p><p>2</p><p> </p><p>	</p><p> =10

Similar questions